Poland’s electricity market. Forecasts of demand for electricity and of electricity prices - Rosicki, Remigiusz (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2018)
The subject of this paper is an analysis of the electricity market in Poland. The period of 2008–2015 came under close scrutiny, whereby emphasis was laid on the trends in electricity generation and demand, while taking into account the country’s economic development. In addition, the text mentions the forecasted demand for electricity in 2030, and electricity prices. As regards electricity prices, both qualitative and quantitative forecasts have been presented. In the latter case, the results of the author’s own forecast have been presented; these were obtained with the aid of selected methods applied for the analysis of the dynamics of economic phenomena (the exponential and linear trend models). In order to make the research problem more specific, the text addresses the following research questions: (1) Is it possible to point out any special characteristics of the structure and operation of the electricity market in Poland? (2) Is it possible to point out a characteristic trend in the changes in demand for electricity in Poland? (3) Is it possible to point out a characteristic trend in the changes in electricity prices in Poland?

Przedmiotem analizy w tekście jest charakterystyka funkcjonowania rynku energii elektrycznej w Polsce. Bardziej szczegółowej analizie poddano lata 2008–2015; położono w niej nacisk na trendy w produkcji i zapotrzebowaniu na energię elektryczną, przy uwzględnieniu rozwoju gospodarczego kraju. Ponadto w tekście uwzględniono prognozy w zakresie zapotrzebowania na energię elektryczną na 2030 r. i prognozy cen na energię elektryczną. W przypadku prognoz cen na energię elektryczną zaprezentowano zarówno prognozę jakościową, jak i ilościową. W ostatnim przypadku zaprezentowano wyniki z własnej prognozy, które uzyskano za pomocą zastosowanych wybranych metod analizy dynamiki zjawisk ekonomicznych (model wykładniczy i model liniowy trendu). W związku z koniecznością uszczegółowienia problemu badawczego w tekście przedstawiono następujące pytania badawcze: (1) Czy można wykazać specyficzne cechy, które charakteryzowałyby strukturę i funkcjonowanie rynku energii elektrycznej w Polsce? (2) Czy można wskazać charakterystyczny trend w zakresie zmian zapotrzebowania na energię elektryczną w Polsce? (3) Czy można wskazać charakterystyczny trend w zakresie zmian cen energii elektrycznej w Polsce?
Rynek energii elektrycznej w Polsce. Prognozy zapotrzebowania na energię elektryczną i prognozy cen energii elektrycznej
Keywords: electricity; electricity market; electricity sector; forecasts of the demand for electricity; forecasts of electricity prices; energia elektryczna; rynek energii elektrycznej; sektor energii elektrycznej; prognozy zapotrzebowania na energię elektryczną; prognozy cen energii elektrycznej